Teachers’ Perception towards Video Conference for Remote Online Teaching: The Use of Google Meet in EFL Elementary Classrooms - Timi Timothy; Anna Marietta da Silva (EDULANGUE, 2022)
Due to the Covid-19 pandemic which occurred in 2020, many schools shifted their traditional classroom teaching to online EFL (English as a foreign language) teaching. Various video conferencing platforms were used to mediate synchronous meetings, including Google Meet. Though research focusing on examining aspects related to various video conferencing platforms has been quite frequent, investigation on teachers’ experience in and perception of online EFL teaching in the primary level using Google Meet has been rather scarce. Therefore, the present study intended to examine EFL teachers’ experience in and perception of EFL teaching using Google Meet. The study made use of focused group discussion which involved the participation of three EFL teachers from a private school in Jakarta. Results revealed that teachers had both positive and negative experiences, such as being able to present learning materials with ease and not being able to monitor students fully. Their perceptions towards using Google Meet for EFL teaching was influenced by these experiences and therefore, were concluded to be mixed since participants perceive the platform to be a source of convenience in various aspects, such as presenting learning materials, while still having limitations such as not enabling teachers to monitor students’ learning progress fully.